2014
DOI: 10.1186/s40781-014-0031-3
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure analysis and effect of inbreeding on body weights at different ages in Iranian Mehraban sheep

Abstract: The objective of this study was to describe the population structure and inbreeding, and to quantify their effects on weights at different ages of Mehraban sheep in Iran. The analysis was based on the pedigree information of 26990 animals and 10278 body weight records from birth to yearling age. Data and pedigree information were collected during 1994 to 2011 by the breeding station of Mehraban sheep. The population structure was analyzed using the CFC program. Inbreeding of all animals was calculated by INBUP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
3
8
3
2
Order By: Relevance
“…Consistent with the low average coancestry between animals in this breed of sheep (0.0072%), Eteqadi et al (2014), Yavarifard et al (2014) and Rochus and Johansson (2017) reported low levels of coancestry in Guilan, Mehraban and Gute sheep breeds, respectively. The average coancestry coefficient could be applied for inbreeding coefficient prediction at subsequent generation; therefore, this parameter would be considered in animal breeding plans (Eteqadi et al 2014).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Consistent with the low average coancestry between animals in this breed of sheep (0.0072%), Eteqadi et al (2014), Yavarifard et al (2014) and Rochus and Johansson (2017) reported low levels of coancestry in Guilan, Mehraban and Gute sheep breeds, respectively. The average coancestry coefficient could be applied for inbreeding coefficient prediction at subsequent generation; therefore, this parameter would be considered in animal breeding plans (Eteqadi et al 2014).…”
Section: Discussionsupporting
confidence: 72%
“…The average coefficients of inbreeding and coancestry were low in Shall sheep. Average inbreeding in this sheep breed (1.62%) was greater than the values reported for Guilan sheep (0.15%, Eteqadi et al 2014), Segureña sheep (0.60%, Barros et al 2017), Dorper sheep (0.32%, Kiya et al 2019) and Lori-Bakhtiari sheep (1.26%, Vatankhah et al 2019), but was lower than the average inbreeding rate in Moghani sheep (2.93%, Ghavi Hossein-Zadeh 2012a), Mehraban sheep (1.69%, Yavarifard et al 2014), Brazilian Morada Nova hair sheep (6.73%, McManus et al 2019), and French dairy sheep (2.34-3.11%, Rodr ıguez-Ramilo et al 2019). The range of inbreeding in the current sheep population (from 0 to 38%) indicated that some matings of close relatives happened, but the number of these types of matings was generally low.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Inbreeding depression emerging as a change in performance per unit of inbreeding increase is generally known as an initial consequence of inbreeding. Inbreeding depression degrades the growth, production, health, reproduction and survival traits [6,7,8,9]. Different breeds, populations and traits apparently vary in terms of their responses to inbreeding [5 and 10].…”
Section: Introductionmentioning
confidence: 99%